Irrigation development in Sri Lanka - Kamaladasa, Bhadra; Institution of Engineers, Sri Lanka ([Colombo] : Institution of Engineers Sri Lanka, 2007)
Evolution and development of irrigation in Sri Lanka.
"Centenary commemoration publications, 1906-2006."
Includes bibliographical references (p. 243).
Keywords: Irrigation -- Sri Lanka -- History